A 50 bp deletion in the SOD1 promoter lowers enzyme expression but is not associated with ALS in Sweden. Issue 5 (17th August 2016) - Ingre, Caroline; Wuolikainen, Anna; Marklund, Stefan L.; Birve, Anna; Press, Rayomand; Andersen, Peter M.
Abstract: Mutations in the superoxide dismutase (SOD1) gene have been linked to amyotrophic lateral sclerosis (ALS). A 50 base pair (bp) deletion of SOD1 has been suggested to reduce transcription and to be associated with later disease onset in ALS. This study was aimed to reveal if the 50 bp deletion influenced SOD1 enzymatic activity, occurrence and phenotype of the disease in a Swedish ALS/control cohort. Blood samples from 512 Swedish ALS patients and 354 Swedish controls without coding SOD1 mutations were analysed for the 50 bp deletion allele. The enzymatic activity of SOD1 in erythrocytes was analysed and genotype-phenotype correlations were assessed. Results demonstrated that the genotype frequencies of the 50 bp deletion were all found to be in Hardy-Weinberg equilibrium. No significant differences were found for age of onset, disease duration or site of onset. SOD1 enzymatic activity showed a statistically significant decreasing trend in the control group, in which the allele was associated with a 5% reduction in SOD1 activity. The results suggest that the 50 bp deletion has a moderate reducing effect on SOD1 synthesis. No modulating effects, however, were found on ALS onset, phenotype and survival in the Swedish population.